Denatonium as a Bitter Taste Receptor Agonist Modifies Transcriptomic Profile and Functions of Acute Myeloid Leukemia Cells - Salvestrini, Valentina; Ciciarello, Marilena; Pensato, Valentina; Simonetti, Giorgia; Laginestra, Maria Antonella; Bruno, Samantha; Pazzaglia, Martina; De Marchi, Elena; Forte, Dorian; Orecchioni, Stefania; Martinelli, Giovanni; Bertolini, Francesco; et al. (Frontiers in Oncology, 2020)
The contribution of cell-extrinsic factors in Acute Myeloid Leukemia (AML) generation and persistence has gained interest. Bitter taste receptors (T2Rs) are G protein-coupled receptors known for their primary role as a central warning signal to induce aversion towards noxious or harmful substances. Nevertheless, the increasing amount of evidence about their extra-oral localization has suggested a wider function in sensing microenvironment, also in cancer settings. In this study, we found that AML cells express functional T2Rs. We also highlighted a significant correlation between the modulation of some TAS2Rs and the poor-prognosis AML groups, i.e. TP53- and TET2-mutated, supporting a potential role of T2Rs in AML cell biology. Gene expression profile analysis showed that T2R activation with the prototypical agonist, denatonium benzoate, significantly modulated a number of genes involved in relevant AML cellular processes. Functional assay substantiated molecular data and indicated that T2R activation reduced AML cell proliferation by inducing cell cycle arrest in G0/G1 phase or induced apoptosis via caspase cascade activation. Moreover, denatonium exposure impaired AML cell motility and migratory capacity, and inhibited cellular respiration by decreasing glucose uptake and oxidative phosphorylation. In conclusion, our results in AML cells expand the observation of cancer T2R expression to the setting of hematological neoplasms and shed light on a role of T2Rs in the extrinsic regulation of leukemia cell functions.